Komersialisasi Anak di Media Sosial: Analisis Konten Akun TikTok Kidfluencer @shabiraalulaadnan - Nugroho, Restu Agung; Amali, Muhammad Thoyib (Unitri Press, 2025)
The kidfluencer phenomenon on social media has become part of a growing digital marketing strategy, including on the TikTok platform. This study aims to analyze the content commercialization process on @shabiraalulaadnan's TikTok account based on the three-stage commercialization model, namely pre-commercialization, commercialization, and post-commercialization. The method used is qualitative content analysis with a descriptive approach, through observation of eight selected videos that display consistent communication patterns. The results show that the commercialization process in this account is carried out systematically. The pre-commercialization stage is marked by the preparation of the script, the use of standard Indonesian language style by children, the storytelling format, and the insertion of light humor that builds closeness with the audience. The commercialization stage can be seen from the contextual integration of products in the narrative, while the post-commercialization stage is marked by a call to action and the use of shopping features on the platform. The novelty of this research lies in the discovery of a distinctive communication style displayed through standard children's language, storytelling consistency, and the use of catchphrases as affective elements that strengthen audience recall and engagement. These findings contribute to the development of digital marketing communication strategy studies through kidfluencer content on social media. Abstrak Fenomena kidfluencer di media sosial telah menjadi bagian dari strategi pemasaran digital yang terus berkembang, termasuk dalam platform TikTok. Penelitian ini bertujuan untuk menganalisis proses komersialisasi konten pada akun TikTok @shabiraalulaadnan berdasarkan model tiga tahap komersialisasi, yaitu pre-commercialization, commercialization, dan post-commercialization. Metode yang digunakan adalah analisis isi kualitatif dengan pendekatan deskriptif, melalui observasi terhadap tigavideo terpilih yang menampilkan pola komunikasi yang konsisten. Hasil penelitian menunjukkan bahwa proses komersialisasi dalam akun ini dilakukan secara sistematis. Tahap pre-commercialization ditandai oleh penyusunan naskah, penggunaan gaya bahasa Indonesia baku oleh anak, format storytelling, serta penyisipan humor ringan yang membangun kedekatan dengan audiens. Tahap commercialization terlihat dari integrasi produk secara kontekstual dalam narasi, sementara tahap post-commercialization ditandai oleh adanya ajakan bertindak dan pemanfaatan fitur belanja dalam platform. Kebaruan dari penelitian ini terletak pada penemuan gaya komunikasi khas yang ditampilkan melalui bahasa baku anak, konsistensi storytelling, serta penggunaan catchphrase sebagai elemen afektif yang memperkuat daya ingat dan keterlibatan audiens. Temuan ini memberikan kontribusi terhadap pengembangan kajian strategi komunikasi pemasaran digital melalui konten kidfluencer di media sosial.